Fungicidal effect of silver nanoparticles on toxigenic fungi in cocoa - Villamizar-Gallardo, Raquel; Osma Cruz, Johann Faccelo; Ortiz-Rodriguez, Oscar Orlando (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the microbicidal effect of silver nanoparticles (AgNPs) on potentially toxigenic fungi affecting cocoa (Theobroma cacao) crops. These fungi, isolated from diseased cocoa pods, were characterized phenotypically and genotypically. The microbicidal effect was assessed by measuring radial mycelial growth, in synthetic culture media, and at different AgNP concentrations in plant tissues. The inhibition effect was monitored in Petri dishes, and changes in fungal structures were observed through scanning electron microscopy. Two potentially toxigenic fungi were highly prevalent: Aspergillus flavus and Fusarium solani. The inhibition assays, performed in liquid and solid synthetic culture media, showed that AgNPs did not significantly affect the growth of these fungi, even at the highest concentration (100 ppm). By contrast, they showed a positive inhibitory effect in plant tissues, especially in the cortex, when infected with A. flavus, in which an 80 ppm dose completely inhibited fungal growth. However, once fungi have managed to penetrate inside the pods, their growth is unavoidable, and AgNP effect is reduced. On F. solani, the studied nanomaterial only induced some texture and pigmentation changes. The microbicidal effect of chemically synthesized silver nanoparticles is greater in plant tissues than in culture media.
Keywords: Aspergillus flavus; Fusarium solani; Theobroma cacao; alternative control; agri-food nanotechnology; ochratoxin A